Comparative Study and Classification of Solar fed Microgrids based on THD, DC component and Sub-harmonics - Das, Tapash Kr; Banik, Ayan; Chattopadhyay, Surajit; Das, Arabinda (International Journal of Computer Sciences and Engineering, 2025)
In this paper, a solar based average model microgrid system has been demonstrated and behaviour of current signals under non identical load conditions have been analyzed. Inverters of various configuarations have been used here to monitor and analysis the performance during rated load, over-load and under- load conditions. First Fourier Transformation (FFT) technique has been applied to assess the nature of inverter output currents. The magnitude of DC components, Total Harmonic Distorsion (THD) and Sub-harmonic components have been evaluated from three phase inverter secondery side currents. Then parameter based comparetive study of microgrid have been carried out at varrying load conditions. Different definite relations have been obtained for a range of no-load to over-load conditions with THD values, magnitude of DC component and sub harmonic frequencies and have been presented.